Aproximación al De Narciso de Pentadio - Mañas Núñez, Manuel (1994)
Pentadius is a late poet and we know nothing about his life. We have some elegies about Fortune, Spring and Narcissus. This work turns around the analysis of the elegy De Narcisso, which is written with versus echoici. Pentadius gets Ovid´s history, but he elaborates it again, and he retouches his verses. Virgil and Martial influyence in the elegy De Narcisso too, only in some verses.
Keywords: Pentadio